Quality indices of groundwater for agricultural use in the Soconusco, Chiapas, Mexico - Santacruz de León, Germán; Ramos Leal, José Alfredo; Morán Ramírez, Janete; López Álvarez, Briseida; Santacruz de León, Eugenio Eliseo (Earth Sciences Research Journal, 2017)
In Soconusco, Chiapas, in spite of the high availability of surface water, it is resorting to the use of groundwater. Knowledge about the quality of surface or groundwater used to irrigate crops in that region is low. This paper aims to contribute to the knowledge of the quality of groundwater for agricultural use through the characterization of the spatial variability. Assuming a random spatial distribution of 45 samples which were collected in situ were determined: acidity and alkalinity (pH), electrical conductivity (EC), Total Dissolved Solids (TDS), cations and anions and trace elements; in addition to the agricultural index: Sodium Adsorption Ratio (SAR), Residual Sodium Carbonate (RSC), Soluble Sodium Percentage (SSP), Sodium Percentage (% Na), Kelly Ratio (KR), Magnesium Adsorption Ratio (MAR), Permeability Index (PI), Effective Salinity (ES), Salinity Potential (SP) and Osmotic Potential (OP). In general, SSP, % Na, KR, PI are low, there is only one anomalous point (9) with high values at W of the study area. Similarly, PS, ES, Cl, Na and SAR are low except point 16 and conversely, RSC and pH are high, except at this point located in the center of the study area. The results allow us to infer that the water in that aquifer presents no problems or sodicity toxic ions. In 27 sites sampled values above 250 µmhos/cm were found at 25°C, classified as medium to high risk of salinity, unsuitable for agricultural use. Analysis of the combined effect of the presence of sodium (SAR) and salinity (EC or TDS) shows that 27 of analyzing sites have restricted water medium at very high for use in irrigation.